The effect of resistance training set configuration on strength and muscular performance adaptations in male powerlifters - Hamid Arazi (Nature Portfolio, 2021)
Abstract The purpose of this study was to determine the effects of different set configurations on strength and muscular performance adaptations after an 8-week resistance training program. Twenty-four male powerlifters participated in this study and were randomly assigned to one of two resistance training groups: (1) cluster sets (CS: n = 8), (2), traditional sets (TS: n = 8), and a control group (CG: n = 8). All powerlifters were evaluated for thigh and arm circumference, upper and lower body impulsive activities, and 1 repetition maximum (1RM) in the back squat, bench press, and deadlift prior to and after the 8-week training intervention. After training, both the CS and TS groups increased arm and thigh circumferences and decreased body fat. The CS group resulted in greater increases in upper and lower body impulsive activities than the TS group, respectively. In addition, the CS and TS groups indicated similar changes in 1RM bench press, back squat, and deadlift following the 8 weeks training intervention. These results suggest that cluster sets induce adaptive changes that favor impulsive activities in powerlifters.